Statistical Characteristics of Flow Field through Open and Semi-Closed Bileaflet Mechanical Heart Valve - Oleksandr Voskoboinyk; Lidiia Tereshchenko; Vladimir Voskoboinick; Gabriela Fernandez; Andrey Voskoboinick; Alberto Redaelli; Gianfranco Beniamino Fiore; Federico Lucherini (Ital Publication, 2020)
The formation of thrombi on the streamlined surface of the bileaflet mechanical heart valves is one of the main disadvantages of such valves. Thrombi block the valve leaflets and disrupt the cardiovascular system. Diagnosis of thrombosis of the bileaflet mechanical heart valves is relevant and requires the creation of effective diagnostic tools. Hydroacoustic registration of the heart noise is one of the methods for diagnosing the operation of a mechanical heart valve. The purpose of the research is to determine the statistical characteristics of the vortex and jet flow through the open and semi-closed bileaflet mechanical heart valve, to identify hydroacoustic differences and diagnostic signs to determine the operating conditions of the valve. Experimental studies were conducted in laboratory conditions on a model of the left atrium and left ventricle of the heart between which there was the bileaflet mechanical heart valve. Hydrodynamic noise was recorded by miniature pressure sensors, which were located downstream of the valve. The vortex and jet flow behind the prosthetic heart valve were non-linear, random processes and were analyzed using the methods of mathematical statistics and probability theory. The integral and spectral characteristics of the pressure field were obtained and the differences in the noise levels and their spectral components near the central and side jets for the open and semi-closed mitral valve were established. It was shown that hydroacoustic measurements could be an effective basis for developing diagnostic equipment for monitoring the bileaflet mechanical heart valve operation.   Doi: 10.28991/SciMedJ-2020-0204-1 Full Text: PDF